2015
DOI: 10.4306/pi.2015.12.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Automated Classification to Predict the Progression of Alzheimer's Disease Using Whole-Brain Volumetry and DTI

Abstract: ObjectiveThis study proposes an automated diagnostic method to classify patients with Alzheimer's disease (AD) of degenerative etiology using magnetic resonance imaging (MRI) markers.MethodsTwenty-seven patients with subjective memory impairment (SMI), 18 patients with mild cognitive impairment (MCI), and 27 patients with AD participated. MRI protocols included three dimensional brain structural imaging and diffusion tensor imaging to assess the cortical thickness, subcortical volume and white matter integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 63 publications
4
19
0
Order By: Relevance
“…A prominent involvement of temporoparietal regions and, to a lesser extent, the frontal lobes has been detected by both region of interest [35,36,37,38] and voxel-based DT MRI studies [39,40,41,42]. Tractography studies in AD showed the presence of diffusion abnormalities in the major limbic tracts, such as the fornix [43,44] and cingulum [45,46], and corticocortical association tracts, such as the corpus callosum (CC) [43,45,47], uncinate [43,45,48], inferior fronto-occipital [43,49], superior longitudinal [43] and inferior longitudinal [43] fasciculi.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…A prominent involvement of temporoparietal regions and, to a lesser extent, the frontal lobes has been detected by both region of interest [35,36,37,38] and voxel-based DT MRI studies [39,40,41,42]. Tractography studies in AD showed the presence of diffusion abnormalities in the major limbic tracts, such as the fornix [43,44] and cingulum [45,46], and corticocortical association tracts, such as the corpus callosum (CC) [43,45,47], uncinate [43,45,48], inferior fronto-occipital [43,49], superior longitudinal [43] and inferior longitudinal [43] fasciculi.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…Typically, DTI studies of gray matter measure mean diffusivity (MD), an indication of the overall magnitude of water diffusion that is independent of direction. Specifically, increased MD has been reported in the hippocampi of: 1) MCI patients versus healthy age-matched controls [10], 2) MCI patients who converted to AD versus those who did not [14,15], 3) AD versus MCI patients [16,17], 4) AD patients versus healthy age-matched controls, and 5) AD patients versus those with another common type of dementia, dementia with Lewy bodies [18]. Further, increased hippocampal MD better predicts impaired verbal memory in MCI patients than decreased hippocampal volume [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, subjects were classified using nonlinear SVM. The procedure was repeated 1000 times, and 2-class based classification accuracy was reported as various percentages between %84.4 and %96.3, in other 3-class based case, performance was %70.5 (±11.5) [6].In 2013, MR images of 345 people from the AddNeuroMed cohort were analyzed with FreeSurfer v4.5.0. The dataset contained 116 AD, 119 MCI, and 110 control samples.…”
Section: Literature Reviewmentioning
confidence: 99%